Andina Physiology - Circulation - pulse, rhythm and form - Monge M., Carlos (1935)
The pulse was one element that was first observed on trips to great heights. It has sought to establish a relationship between height and pulse rate while this was studied during the trip. At present - where effortless ascents or airplane - it is shown that such an event, but under certain conditions of rarefied air. We can say, as a result of our observations, this frequency is relatively moderate and only when signs appear normal Soroche to appear more or less intense tachycardia rhythm breaks.